Synthesis of a biocomposite based on Kluwih (Artocarpus camansi) seed starch incorporated with carrageenan as a functional additive and cellulose nanofiber filler - Fadlan Hidayat; Eti Indarti; Rahmi; Nasrul Arahman (Case Studies in Chemical and Environmental Engineering)
The widespread use of synthetic plastics causes environmental issues because of their nondegradability. In this study, biocomposite from Kluwih seed starch were incorporated with carrageenan and cellulose nanofiber (CNF) to improve their mechanical properties. CNFs were prepared using the TEMPO method with ultrasonication. The variables included starch (1, 1.5, 2 g), carrageenan (3, 4.5, 6 g), and CNF (0.006, 0.12, 0.18 g). The mechanical properties of the biocomposite were optimized using RSM. Zeta potential analysis confirmed the stability of CNFs, and XRD and FTIR analyses revealed improved crystallinity and functional groups. The tensile strength of the biocomposites was 12.08 kgf/mm2, which is suitable for sustainable packaging applications.